My Father’s Song: Interaction Design Installation - Karlen, Joan (Mimesis Journal, 2024)
In My Father’s Song: Interaction Design Installation, the choreographer and media artist invites participation with and submersion in a digital media landscape, contributing to a wider range of ways of appreciating and understanding the intersections between our tangible and intangible heritages. The installation juxtaposes large-scale public projection with private experience, and reflective content with the grandeur of nature, the elements, ancestry and generation. Interacting with a Kinect Xbox, the user makes editing decisions in real time – drawing and overlaying cursive and block text poetry, changing video dimensions and generating animated leaves from their fingertips. During each immersive installation cycle the video scenes appear in a new, randomized order; the work is never the same twice. At the Banff Centre, the artist’s research included creating software code that could mix, in real time, video with other digital elements via interactive participation. Conceived for projection in large screen installations and exhibitions, the artist conceived, recorded and edited the 19 video scenes with themes that examine generation, scale, and nature’s elemental cycles – from clouds to mist, from snowflakes to water; from leafy aspens shimmering in the wind, to leaves falling and returning to earth. Adding to their experience, user participants are able to overlay two poems, in block and cursive text – “My Father’s Song” by Simon J. Ortiz describes generational lessons, and “The Flap of the Wallet” by Jalal al-Din Rumi explores metaphors about nature and the elements to unveil the timeless beauty and mysteries of life.